Carbon sequestration and climate change impact on the yield of Bagras (Eucalyptus deglupta Blume) in Bigras-Corn boundary planting agroforestry system in Misamis Oriental and Bukidnon, Philippines - Palma, Richmund A. (Journal of Environmental Science and Management, 2014)
Bagras-corn coundary planting agroforestry system for biomass production and climate change mitigation is essential options for smallholder agroforestry farms in Misamis Oriental and Bukidnon, Philippines. In this study, the multiple linear regression analysis was used to develop an appropriate prediction models for yield and biomass expansion factor from soil chemical properties, physiographic charasteristics, stand attributes, rainfall and temperature. Results showed strong association of age, site index, temperature and spacing with yield (88.7%). Based on the model, the predicted biomass accumulation at 52 trees per hectare was 24.44. 73.07 and 78.67 Mg ha-1. The mean annual aboveground biomass accumulation was 24.44, 7.31 and 3.93 Mgha-1 y1 at ages 1, 10 and 20 years. The equation developed had shown the predicted positive response of bagras to future changes in seasonal mean temperature. Establishing bagras at d distance of 2 m, site index equal to 19 m, age set at 10 y was predicted to yield 0.1974 m3 per tree in 2020. At 2050, yield was predicted to balloon to approximately 3.1182m3 per tree. Yield and biomass production in boundary plantings can be highly variable-dependent on environmental and soil characteristics and tree spacing.